1997
DOI: 10.1038/sj.bjp.0701126
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the contractile effects and binding kinetics of endothelin‐1 and sarafotoxin S6b in rat isolated renal artery

Abstract: 1 To date, only two mammalian endothelin (ET) receptors, termed ET A and ET B , have been cloned, sequenced and characterized. However, several functional studies of isolated blood vessels suggest that ET-1-induced contractions may be mediated by multiple ET A receptors. In this study, the ET A receptors in renal arteries isolated from Wistar rats were characterized by isometric tension recording and radioligand binding techniques. 2 ET-1, sarafotoxin S6b (StxS6b) and ET-3 produced concentration-dependent cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…31 ET B receptors have also been detected in be explained in terms of differences in the kinetics of ovine airway smooth muscle cells in culture, 56 although particular receptor-ligand interactions. 54 In the abthis is related to passage-associated cell phenotype sence of support from molecular cloning, structural, changes. 57 In contrast, ET A and ET B receptors were operational and signal transduction data, the conpresent in approximately equal proportions in rat clusion that such subtypes exist must be viewed as and mouse isolated airway smooth muscle and both unproven.…”
Section: Et Receptor/ligand Interactionsmentioning
confidence: 99%
“…31 ET B receptors have also been detected in be explained in terms of differences in the kinetics of ovine airway smooth muscle cells in culture, 56 although particular receptor-ligand interactions. 54 In the abthis is related to passage-associated cell phenotype sence of support from molecular cloning, structural, changes. 57 In contrast, ET A and ET B receptors were operational and signal transduction data, the conpresent in approximately equal proportions in rat clusion that such subtypes exist must be viewed as and mouse isolated airway smooth muscle and both unproven.…”
Section: Et Receptor/ligand Interactionsmentioning
confidence: 99%
“…Recent research in isolated, hydronephrotic kidneys has provided evidence that ET A receptors are important for constriction of preglomerular vessels, whilst ET B receptors are important for mediating constriction of both preglomerular vessels and efferent arterioles ( Endlich et al ., 1996 ). In isolated, main branches of the renal artery, in vitro studies have demonstrated the presence of ET A receptors and absence of ET B receptors ( Clark & Pierre, 1995 ; Devadason & Henry, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Functional ET-1 receptors have been characterized in the rat renal vasculature. In the isolated rat main branch of the renal artery, the contraction to ET-1 is mediated by ET A receptors, whereas ET B receptors do not appear to be present [32,33]. However, from in vivo studies, there is evidence that both ET A and ET B receptors contribute to the constriction of the rat renal microvasculature [34].…”
Section: Introductionmentioning
confidence: 99%